Polycaffeic acid interlayer MAF-6-based mixed matrix membrane as well as preparation method and application thereof
By increasing the MAF-60 % core point in the use of polycal coffee acid expansion in the permeable vaporization film, the MAF-6 particles have been solved in the lack of core points in the porous polymer membrane, and the efficient ethanol-water separation is achieved, and the water separation is enhanced. The permeability and separators of the membrane.
Patent Information
- Application Number
- CN202411323463.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-23
AI Technical Summary
There is a trade-off between permeability and selectivity in ethanol-water separation of existing permeability membranes, and the MAF-6 particles are insufficient nucleation sites in porous polymer membranes, resulting in poor membrane performance.
The MAF-60 % core point is increased by polyca-coffee sterilization. The MAF-6 is growing in situ on the PVDF bottom membrane, and a polycal acid expansion is formed on it, combining the polymer matrix layer to form a mixed matrix membrane.
Improving the permeability and separators of the membrane, enhancing the adhesion capacity of MAF-6 and gel layer, reducing membrane defects, improving separation performance, and controlling the thickness of the membrane.
Smart Images

Figure BDA0005054692690000031 
Figure HDA0005054692700000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of pervaporation membranes, and in particular to a polycaffeic acid sandwich MAF-6-based mixed matrix membrane and a preparation method thereof, as well as application of the membrane in ethanol-water separation. Background Art
[0002] Pervaporation membrane is an excellent membrane separation technology. It has the advantages of simple operation, low energy consumption, and good environmental protection. It has high separation efficiency for dehydration of organic matter and recovery of organic matter in water. At present, the most widely studied hotspot is the mixed matrix membrane in which MOF / COF and inorganic nanoparticles are loaded in a polymer matrix. Among them, MOFs have good development prospects in mixed matrix membranes due to their high specific surface area, thermal stability, and preferential adsorption of specific molecules.
[0003] MAF-6 with RHO topology is a Zn 2+ As the metal source, 2-ethylimidazole is a hydrophobic large-pore MOF. In particular, both the inner pores and the outer crystal surface of MAF-6 are highly hydrophobic, which is different from ZIF-8. Due to its high hydrophobicity, it can hardly adsorb water or be wetted by water, but it can easily adsorb a large number of organic molecules. In addition, MAF-6 nanoparticles can be synthesized at room temperature through a rapid solution mixing reaction with high crystallinity, high purity, large quantity and high thermal / chemical stability. However, MAF-6 particles still face problems such as poor adhesion and compatibility with the carrier and lack of sufficient nucleation sites in porous polymer membranes. Sol-gel coating is a simple method to improve the nucleation sites, and organic materials are more likely to form a continuous and uniform layer on the substrate. Its rich functional groups are also conducive to the close combination of the separation layer and the substrate. Caffeic acid is a natural plant polyphenol with a catechol structure and a carboxyl group. At the same time, caffeic acid itself can be oxidized and polymerized to form a layer of organic macromolecules. Summary of the invention
[0004] In order to break the trade-off between permeation flux and selectivity, improve pervaporation performance, and prepare a uniform and defect-free membrane, the present invention provides a defect-free mixed matrix membrane with polycaffeic acid as an interlayer to improve MAF-6 nucleation sites, a preparation method thereof, and application in ethanol-water separation.
[0005] The technical solution of the present invention is as follows:
[0006] A polycaffeic acid interlayer MAF-6-based mixed matrix membrane, which is composed of a PVDF (polyvinylidene fluoride) base membrane, a polycaffeic acid interlayer with MAF-6 grown in situ, and a polymer matrix layer with MAF-6 dispersed therein, from bottom to top;
[0007] The polymer matrix is selected from: polyether block polyamide, polydimethylsiloxane, phenyltrimethoxysilane, preferably polyether block polyamide;
[0008] The polycaffeic acid is prepared by polymerization of caffeic acid, ammonium persulfate and ethylenediamine; preferably, the particle size of the polycaffeic acid is 200 to 1000 nm;
[0009] Specifically, the preparation method of polycaffeic acid is as follows:
[0010] The aqueous solution of caffeic acid, ammonium persulfate and ethylenediamine are mixed evenly, the pH is adjusted to 6-7, and the mixture is stirred and reacted at room temperature for 2 hours. The reaction solution is then centrifuged, and the precipitate is collected, washed and dried to obtain polycaffeic acid.
[0011] The molar ratio of caffeic acid, ammonium persulfate and ethylenediamine is 2-4:1-2:1, preferably 2:1:1;
[0012] The concentration of the aqueous solution of caffeic acid is 1 to 5 g / L, preferably 2 g / L.
[0013] The method for preparing the polycaffeic acid sandwich MAF-6 based mixed matrix membrane of the present invention comprises the following steps:
[0014] (1) Dispersing polycaffeic acid uniformly in deionized water, adding an ammonia solution of zinc hydroxide to adjust the pH to 6-7, and then adding an organic solution of 2-ethylimidazole to disperse uniformly to obtain a mixed system; immersing a PVDF substrate in the obtained mixed system, allowing it to stand for 1-4 hours, then taking it out and rinsing it with methanol, and drying it at room temperature to obtain a polycaffeic acid membrane of in-situ grown MAF-6;
[0015] The mass ratio of polycaffeic acid, zinc hydroxide and 2-ethylimidazole is 1-20:10-20:10, preferably 10:25:23.75;
[0016] The volume mass ratio of deionized water to polycaffeic acid is 16.7 to 33.3:1, mL / g, preferably 25:1, mL / g;
[0017] In the aqueous solution of zinc hydroxide, the concentration of zinc hydroxide is 40 to 80 g / L, preferably 50 g / L; the concentration of the aqueous ammonia solvent is 15 to 28 wt%;
[0018] In the organic solution of 2-ethylimidazole, the concentration of 2-ethylimidazole is 5 to 20 g / L, preferably 11.8 g / L; the solvent is a mixed solvent of methanol and cyclohexane in a volume ratio of 15:1, wherein cyclohexane is added as a hydrophobic template;
[0019] The content of polycaffeic acid on PVDF substrate ranges from 20 to 50 g / m 2 , preferably 23g / m 2 ;
[0020] The pH can be adjusted by using 7.5 mol / L hydrochloric acid and 0.1 mol / L sodium hydroxide aqueous solution;
[0021] (2) MAF-6 was dispersed in n-butanol, and then the polymer matrix was added, stirred (80°C, 5 h), and allowed to stand (60°C, 12 h) to obtain a membrane-building solution;
[0022] The mass ratio of MAF-6, polymer matrix, and n-butanol is 0.01-0.2:1:15-20;
[0023] (3) fixing the polycaffeic acid film of the in-situ grown MAF-6 obtained in step (1), applying the membrane-building solution obtained in step (2) by scraping, and drying to obtain the polycaffeic acid sandwich MAF-6-based mixed matrix membrane;
[0024] The coating thickness of the film-building liquid is controlled at 50 to 100 μm.
[0025] The polycaffeic acid sandwich MAF-6-based mixed matrix membrane of the present invention can be used for pervaporation recovery of alcohol in alcohol aqueous solution; the alcohol is preferably ethanol.
[0026] The specific application method is:
[0027] At 40°C, a polycaffeic acid sandwich MAF-6-based mixed matrix membrane was horizontally fixed in a closed container, and the membrane separated the closed container into two independent spaces (such as Figure 1 As shown in FIG. 1 , the front side of the membrane is in contact with the alcohol aqueous solution, and the gas (including air and alcohol) is continuously extracted from the top of the other side, and the alcohol is recovered by condensation;
[0028] Preferably, the alcohol aqueous solution is an ethanol aqueous solution with a concentration of 5 wt %; the ethanol aqueous solution with a concentration of 5 wt % is used as the permeation side feed liquid, and the operating conditions of the pervaporation are: temperature 40° C., the upper vacuum degree 100 Pa, and the feed rate 0.4 L / min.
[0029] Compared with the prior art, the innovation and advantages of the present invention are as follows:
[0030] (1) For the first time, cheap and readily available caffeic acid was applied to mixed matrix membrane separation of ethanol / water, which broadened the application field of caffeic acid in membrane separation.
[0031] (2) Caffeic acid was first combined with MAF-6, and multiple phenolic hydroxyl groups and amino groups on caffeic acid were combined with Zn 2+ Cross-linking to form a metal complex-polyphenol network, pre-seeding MAF-6 seeds on the gel layer, enhancing the adhesion of MAF-6 to the gel layer, and increasing the nucleation sites.
[0032] (3) After a layer of polymer-based membrane-building liquid is scraped on, the hydrophobicity of the membrane surface is improved, and at the same time, it has good compatibility and can greatly reduce the defects of the membrane. It not only effectively improves the separation performance of the membrane, but also controls the thickness of the membrane and increases its permeation flux.
[0033] (4) The polycaffeic acid sandwich MAF-6-based mixed matrix membrane involved in the present invention can be effectively used in the field of ethanol / water separation. Compared with other separation methods, it has the advantages of simple preparation, environmental friendliness, small required space, high separation efficiency, etc. The prepared defect-free mixed matrix membrane has good pervaporation performance during ethanol / water separation, and has good application prospects for future bio-alcohol recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 : Schematic diagram of the pervaporation device for detecting membrane performance of the present invention. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Without departing from the content and scope of the present invention, changes in implementation should be included in the technical scope of the present invention.
[0036] In the following embodiments:
[0037] The pervaporation performance of the membrane is evaluated by two parameters: permeation flux (J) and separation factor (α), which are calculated using the following formula:
[0038]
[0039] Where m is the total mass collected on the permeate side after t hours, A is the effective membrane area (7 cm 2 ), X and Y are the mass fractions of ethanol in the feed solution and the permeate, respectively.
[0040] In the following examples, the PVDF ultrafiltration membrane used was manufactured by Zhongke Ruiyang Membrane Technology (Beijing) Co., Ltd., with a product number of SG-UF050-8084, a molecular weight cutoff of 50,000 Da, and an area of about 10 cm 2 .
[0041] The polyether block polyamide was purchased from Arkema, France, with the product number PEBAX MH 1657.
[0042] Polydimethylsiloxane was purchased from Jinan Xingchi Chemical Co., Ltd. with a product number of XC-107 and a viscosity of 100,000 cst.
[0043] Embodiment 1:
[0044] (1) Preparation of polycaffeic acid: 1 g of caffeic acid was completely dissolved in deionized water at 80°C to obtain a caffeic acid solution with a concentration of 2 g / L. Then ammonium persulfate and ethylenediamine were added in sequence, with a molar ratio of caffeic acid, ammonium persulfate, and ethylenediamine of 2:1:1, wherein the mass of ammonium persulfate was 0.633 g and the mass of ethylenediamine was 188 μL, and the mixture was stirred until uniformly mixed. Hydrochloric acid (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) The pH was adjusted to 6-7. The polymerization reaction was carried out under stirring at room temperature for 2 hours, and then centrifuged. The precipitate was filtered and washed with deionized water, and dried at 80° C. for 12 hours. The mass of the obtained polycaffeic acid was 0.7834 g.
[0045] Preparation of MAF-6: 1g zinc hydroxide was completely dissolved in 20ml ammonia water (25wt%) to obtain zinc hydroxide solution A dissolved in ammonia water, 1.9g 2-ethylimidazole was dissolved in a mixed solution of 150ml methanol and 10ml cyclohexane, and stirred evenly to obtain 2-ethylimidazole solution B. Solution A was quickly poured into solution B, stirred at room temperature for 2h, vacuum filtered and washed with methanol, and dried at 80°C for 12h. The mass of the obtained MAF-6 was 1.170g.
[0046] (2) In-situ growth of MAF-6 on polycaffeic acid substrate: 0.4 g polycaffeic acid was dispersed in 10 ml deionized water; 1 g zinc hydroxide was dissolved in 20 ml ammonia water (25 wt%) and stirred to obtain zinc hydroxide solution C dissolved in ammonia water. 0.95 g 2-ethylimidazole was dissolved in a mixed solution of 75 ml methanol and 5 ml cyclohexane and stirred to obtain 2-ethylimidazole solution D.
[0047] Slowly add the zinc hydroxide solution C dissolved in ammonia water to the polycaffeic acid solution prepared above, and add HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) to a pH of 6-7 to obtain a mixed solution. Add 2-ethylimidazole solution D to the prepared mixed solution and stir evenly to obtain 85 mL of a solution. Immerse the PVDF base membrane in the above solution and let it stand for 4 hours. Take out the membrane, rinse it gently with methanol, and let it stand at room temperature.
[0048] (3) Preparation of membrane casting solution: 0.1 g MAF-6 was dispersed in 18.4 g n-butanol, stirred at 80° C. for 6 h (preferably at 800 rpm), and ultrasonicated for 2 h, then 1 g polyether block polyamide was added to obtain a membrane casting solution, which was stirred at 80° C. for 5 h to ensure that MAF-6 was evenly dispersed. The solution was allowed to stand at 60° C. for 12 h to remove bubbles.
[0049] (4) Preparation of polycaffeic acid interlayer MAF-6-based mixed matrix membrane: The precursor membrane prepared in step (2) was fixed on a smooth glass plate, and then the membrane-building solution prepared in step (3) was slowly poured on the membrane surface and scraped (the coating device was set to a thickness of 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80° C. for drying for 12 hours. The obtained membrane was the aforementioned polycaffeic acid interlayer MAF-6-based mixed matrix membrane.
[0050] The prepared polycaffeic acid sandwich MAF-6 based mixed matrix membrane (one side of the membrane coating liquid is in contact with the permeate side feed liquid) is used in the separation of volatile organic compounds as follows:
[0051] The ethanol / water solution with a concentration of 5wt% was used as the permeation side feed liquid. The operating conditions of pervaporation were as follows: temperature 40℃, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 2160g·m -2 ·h -1 , the separation factor is 15.3.
[0052] Embodiment 2:
[0053] (1) Preparation of polycaffeic acid: 1 g of caffeic acid was completely dissolved in deionized water at 80°C to obtain a caffeic acid solution with a concentration of 2 g / L. Then ammonium persulfate and ethylenediamine were added in sequence, with a molar ratio of caffeic acid, ammonium persulfate, and ethylenediamine of 2:1:1, wherein the mass of ammonium persulfate was 0.633 g and the mass of ethylenediamine was 188 μL, and the mixture was stirred until uniformly mixed. HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) adjust the pH to 6-7. After the polymerization reaction is carried out at room temperature for 2 hours with stirring, the obtained precipitate is centrifuged, filtered and washed with deionized water, and dried at 80° C. for 12 hours. The concentration of the caffeic acid solution is 2 g / L. The mass of the obtained polycaffeic acid is 0.7834 g.
[0054] Preparation of MAF-6: 1g zinc hydroxide was completely dissolved in 20ml ammonia water (25wt%) to obtain zinc hydroxide solution A dissolved in ammonia water, 1.9g 2-ethylimidazole was dissolved in a mixed solution of 150ml methanol and 10ml cyclohexane, and stirred evenly to obtain 2-ethylimidazole solution B. Solution A was quickly poured into solution B, stirred at room temperature for 2h, vacuum filtered and washed with methanol, and dried at 80°C for 12h. The mass of the obtained MAF-6 was 1.170g.
[0055] (2) In-situ growth of MAF-6 on polycaffeic acid substrate: 0.4 g polycaffeic acid was dispersed in 10 ml deionized water; 1 g zinc hydroxide was dissolved in 20 ml ammonia water (25 wt%) and stirred to obtain zinc hydroxide solution C dissolved in ammonia water. 4 g 2-ethylimidazole was dissolved in a mixed solution of 50 ml methanol and 5 ml cyclohexane and stirred to obtain 2-ethylimidazole solution D.
[0056] The above zinc hydroxide solution C dissolved in ammonia water was slowly added to the polycaffeic acid solution prepared above, and HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) to a pH of 6-7 to obtain a mixed solution. Add 25 ml of 2-ethylimidazole solution D to the prepared mixed solution and stir evenly to obtain 55 mL of solution. Immerse the PVDF base membrane in the above solution and let it stand for 4 hours. Take out the membrane, rinse it gently with methanol, and let it stand at room temperature.
[0057] (3) Preparation of film casting solution: 0.15 g MAF-6 was dispersed in 18.4 g n-butanol, stirred at 80° C. for 6 h (preferably at 800 rpm), and ultrasonicated for 2 h, then 1 g polyether block polyamide was added to obtain a casting solution, which was stirred at 80° C. for 5 h to ensure that MAF-6 was evenly dispersed. The solution was allowed to stand at 60° C. for 12 h to remove bubbles.
[0058] (4) Preparation of polycaffeic acid interlayer MAF-6-based mixed matrix membrane: The precursor membrane prepared in step (2) was fixed on a smooth glass plate, and then the membrane-building solution prepared in step (3) was slowly poured on the membrane surface and scraped (the coating device was set to a thickness of 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80° C. for drying for 12 hours. The obtained membrane was the aforementioned polycaffeic acid interlayer MAF-6-based mixed matrix membrane.
[0059] The prepared polycaffeic acid sandwich MAF-6 based mixed matrix membrane (one side of the membrane coating liquid is in contact with the permeate side feed liquid) is used in the separation of volatile organic compounds as follows:
[0060] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 2020g·m -2 ·h -1 , the separation factor is 15.6.
[0061] Embodiment 3:
[0062] (1) Preparation of polycaffeic acid: 1 g of caffeic acid was completely dissolved in deionized water at 80°C to obtain a caffeic acid solution with a solubility of 2 g / L. Then ammonium persulfate and ethylenediamine were added in sequence, with a molar ratio of caffeic acid, ammonium persulfate, and ethylenediamine of 2:1:1, wherein the mass of ammonium persulfate was 0.633 g and the mass of ethylenediamine was 188 μL, and the mixture was stirred until uniformly mixed. HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) adjust the pH to 6-7. After the polymerization reaction is carried out at room temperature for 2 hours with stirring, the obtained precipitate is centrifuged, filtered and washed with deionized water, and dried at 80° C. for 12 hours. The concentration of the caffeic acid solution is 2 g / L. The mass of the obtained polycaffeic acid is 0.7834 g.
[0063] Preparation of MAF-6: 1g zinc hydroxide was completely dissolved in 20ml ammonia water (25wt%) to obtain zinc hydroxide solution A dissolved in ammonia water, 1.9g 2-ethylimidazole was dissolved in a mixed solution of 150ml methanol and 10ml cyclohexane, and stirred evenly to obtain 2-ethylimidazole solution B. Solution A was quickly poured into solution B, stirred at room temperature for 2h, vacuum filtered and washed with methanol, and dried at 80°C for 12h. The mass of the obtained MAF-6 was 1.170g.
[0064] (2) In-situ growth of MAF-6 on polycaffeic acid substrate: 0.4 g polycaffeic acid was dispersed in 10 ml deionized water; 1.6 g zinc hydroxide was dissolved in 20 ml ammonia water (25 wt%) (the concentration of the zinc hydroxide solution was 80 g / L), and stirred evenly to obtain a zinc hydroxide solution C dissolved in ammonia water. 4 g 2-ethylimidazole was dissolved in a mixed solution of 50 ml methanol and 5 ml cyclohexane, and stirred evenly to obtain a 2-ethylimidazole solution D.
[0065] Slowly add the zinc hydroxide solution C dissolved in ammonia water to the polycaffeic acid solution prepared above, and add HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) to a pH of 6-7 to obtain a mixed solution. Add 25 ml of 2-ethylimidazole solution D to the prepared mixed solution and stir evenly to obtain 55 mL of solution. Immerse the PVDF base membrane in the above solution and let it stand for 4 hours. Take out the membrane, rinse it gently with methanol, and let it stand at room temperature.
[0066] (3) Preparation of membrane casting solution: 0.1 g MAF-6 was dispersed in 18.4 g n-butanol, stirred at 80° C. for 6 h (preferably at 800 rpm), and ultrasonicated for 2 h, then 1 g polyether block polyamide was added to obtain a membrane casting solution, which was stirred at 80° C. for 5 h to ensure that MAF-6 was evenly dispersed. The solution was allowed to stand at 60° C. for 12 h to remove bubbles.
[0067] (4) Preparation of polycaffeic acid interlayer MAF-6-based mixed matrix membrane: The precursor membrane prepared in step (2) was fixed on a smooth glass plate, and then the membrane-building solution prepared in step (3) was slowly poured on the membrane surface and scraped (the coating device was set to a thickness of 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80° C. for drying for 12 hours. The obtained membrane was the aforementioned polycaffeic acid interlayer MAF-6-based mixed matrix membrane.
[0068] The prepared polycaffeic acid sandwich MAF-6 based mixed matrix membrane (one side of the membrane coating liquid is in contact with the permeate side feed liquid) is used in the separation of volatile organic compounds as follows:
[0069] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 1588g·m -2 ·h -1 , the separation factor is 16.7.
[0070] Embodiment 4:
[0071] (1) Preparation of polycaffeic acid: 1 g of caffeic acid was completely dissolved in deionized water at 80°C to obtain a caffeic acid solution with a solubility of 2 g / L. Then ammonium persulfate and ethylenediamine were added in sequence. The molar ratio of caffeic acid, ammonium persulfate, and ethylenediamine was 2:1:1, with 0.633 g of ammonium persulfate and 188 μL of ethylenediamine. Stir until uniformly mixed. Add HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) The pH was adjusted to 6-7. After the polymerization reaction was carried out at room temperature for 2 hours, the precipitate was centrifuged, filtered and washed with deionized water, and dried at 80° C. for 12 hours. The mass of the obtained polycaffeic acid was 0.7834 g.
[0072] Preparation of MAF-6: 1g zinc hydroxide was completely dissolved in 20ml ammonia water (25wt%) to obtain zinc hydroxide solution A dissolved in ammonia water, 1.9g 2-ethylimidazole was dissolved in a mixed solution of 150ml methanol and 10ml cyclohexane, and stirred evenly to obtain 2-ethylimidazole solution B. Solution A was quickly poured into solution B, stirred at room temperature for 2h, vacuum filtered and washed with methanol, and dried at 80°C for 12h. The mass of the obtained MAF-6 was 1.170g.
[0073] (2) In-situ growth of MAF-6 on polycaffeic acid substrate: 0.5 g polycaffeic acid was dispersed in 10 ml deionized water; 1 g zinc hydroxide was dissolved in 20 ml ammonia water and stirred evenly to obtain zinc hydroxide solution C dissolved in ammonia water. 4 g 2-ethylimidazole was dissolved in a mixed solution of 50 ml methanol and 5 ml cyclohexane and stirred evenly to obtain 2-ethylimidazole solution D.
[0074] Slowly add the zinc hydroxide solution C dissolved in ammonia water to the polycaffeic acid solution prepared above, and add HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) to a pH of 6-7 to obtain a mixed solution. Add 25 ml of 2-ethylimidazole solution D to the prepared mixed solution and stir evenly to obtain 55 mL of solution. Immerse the PVDF base membrane in the above solution and let it stand for 4 hours. Take out the membrane, rinse it gently with methanol, and let it stand at room temperature.
[0075] (3) Preparation of membrane casting solution: 0.1 g MAF-6 was dispersed in 18.4 g n-butanol, stirred at 80° C. for 6 h (preferably at 800 rpm), and ultrasonicated for 2 h, then 1 g polyether block polyamide was added to obtain a membrane casting solution, which was stirred at 80° C. for 5 h to ensure that MAF-6 was evenly dispersed. The solution was allowed to stand at 60° C. for 12 h to remove bubbles.
[0076] (4) Preparation of polycaffeic acid interlayer MAF-6-based mixed matrix membrane: The precursor membrane prepared in step (2) was fixed on a smooth glass plate, and then the membrane-building solution prepared in step (3) was slowly poured on the membrane surface and scraped (the coating device was set to a thickness of 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80° C. for drying for 12 hours. The obtained membrane was the aforementioned polycaffeic acid interlayer MAF-6-based mixed matrix membrane.
[0077] The prepared polycaffeic acid sandwich MAF-6 based mixed matrix membrane (one side of the membrane coating liquid is in contact with the permeate side feed liquid) is used in the separation of volatile organic compounds as follows:
[0078] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 2347g·m -2 ·h -1 , the separation factor is 13.
[0079] Embodiment 5:
[0080] (1) Preparation of polycaffeic acid: 1 g of caffeic acid was completely dissolved in deionized water at 80°C to obtain a caffeic acid solution with a solubility of 2 g / L. Then ammonium persulfate and ethylenediamine were added in sequence, with a molar ratio of caffeic acid, ammonium persulfate, and ethylenediamine of 2:1:1, wherein the mass of ammonium persulfate was 0.633 g and the mass of ethylenediamine was 188 μL, and the mixture was stirred until uniformly mixed. HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1 ) The pH was adjusted to 6-7. After the polymerization reaction was carried out at room temperature for 2 hours, the precipitate was centrifuged and washed with deionized water, and dried at 80° C. for 12 hours. The mass of the obtained polycaffeic acid was 0.7834 g.
[0081] Preparation of MAF-6: 1g zinc hydroxide was completely dissolved in 20ml ammonia water (25wt%) to obtain zinc hydroxide solution A dissolved in ammonia water, 1.9g 2-ethylimidazole was dissolved in a mixed solution of 150ml methanol and 10ml cyclohexane, and stirred evenly to obtain 2-ethylimidazole solution B. Solution A was quickly poured into solution B, stirred at room temperature for 2h, vacuum filtered and washed with methanol, and dried at 80°C for 12h. The mass of the obtained MAF-6 was 1.170g.
[0082] (2) In-situ growth of MAF-6 on polycaffeic acid substrate: 0.4 g polycaffeic acid was dispersed in 10 ml deionized water; 1 g zinc hydroxide was dissolved in 20 ml ammonia water and stirred evenly to obtain zinc hydroxide solution C dissolved in ammonia water. 4 g 2-ethylimidazole was dissolved in a mixed solution of 50 ml methanol and 5 ml cyclohexane and stirred evenly to obtain 2-ethylimidazole solution D.
[0083] The above zinc hydroxide solution C dissolved in ammonia water was slowly added to the polycaffeic acid solution prepared above, and HCl (7.5 mol·L -1 ) and sodium hydroxide aqueous solution (0.1 mol·L -1) to a pH of 6-7 to obtain a mixed solution. Add 25 ml of 2-ethylimidazole solution D to the prepared mixed solution and stir evenly to obtain 55 mL of solution. Immerse the PVDF base membrane in the above solution and let it stand for 4 hours. Take out the membrane, rinse it gently with methanol, and let it stand at room temperature.
[0084] (3) Preparation of membrane-building solution: 0.855 g of polydimethylsiloxane was dispersed in 5 ml of organic solvent n-heptane. After sufficient dispersion, 0.855 g of MAF-6 prepared in (1) was added and stirred for 30 min. 92 μL of silane coupling agent and 0.0085 g of catalyst were added in sequence. The mixture was stirred at room temperature for 4 h. The obtained polymer matrix was allowed to stand for degassing to obtain a membrane-building solution. The crosslinking agent was tetraethyl orthosilicate; the catalyst was dibutyltin dilaurate; the mass ratio of polydimethylsiloxane, crosslinking agent and catalyst was 100:10:1.
[0085] (4) Preparation of polycaffeic acid interlayer MAF-6-based mixed matrix membrane: The precursor membrane prepared in step (2) was fixed on a smooth glass plate, and then the membrane-building solution prepared in step (3) was slowly poured on the membrane surface and scraped (the coating device was set to a thickness of 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80° C. for drying for 12 hours. The obtained membrane was the aforementioned polycaffeic acid interlayer MAF-6-based mixed matrix membrane.
[0086] The prepared polycaffeic acid sandwich MAF-6 based mixed matrix membrane (one side of the membrane coating liquid is in contact with the permeate side feed liquid) is used in the separation of volatile organic compounds as follows:
[0087] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 1807g·m -2 ·h -1 , the separation factor is 15.1.
[0088] Comparative Example 1:
[0089] (1) Preparation of membrane casting solution: Weigh 18.4 g of n-butanol solution, add 1 g of polyether block polyamide to obtain a membrane casting solution, stir the membrane casting solution at 80° C. for 5 h, and stand at 60° C. for 12 h to remove bubbles.
[0090] (2) Preparation of membrane: The PVDF base membrane was fixed on a smooth glass plate, and then the membrane-building solution prepared in (1) was slowly poured onto the membrane surface and scraped (the coating thickness was set to 60 μm). After scraping, the membrane was placed in a culture dish and dried in an oven at 80°C for 12 hours. The obtained membrane was a polyether block polyamide matrix pervaporation membrane.
[0091] The prepared polyether block polyamide matrix pervaporation membrane (one side of the membrane coating liquid is in contact with the permeation side feed liquid) is used in the separation of volatile organic compounds as follows:
[0092] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 1390g·m -2 ·h -1 , the separation factor is 8.8.
[0093] This phenomenon is due to the fact that the membrane is composed of only one layer of polyether block polyamide, the hydrophobicity of the membrane surface is insufficient, and there are relatively few transmission paths for alcohol molecules. The addition of highly hydrophobic MAF-6 and polycaffeic acid interlayers can increase the selectivity for alcohol preferential permeation. At the same time, the high specific surface area of MAF-6 itself provides more paths for ethanol molecules to pass through, thereby increasing the permeation flux.
[0094] Comparative Example 2:
[0095] (1) Preparation of polycaffeic acid: 1 g of caffeic acid was completely dissolved in deionized water at 80°C to obtain a caffeic acid solution with a solubility of 2 g / L. Then ammonium persulfate and ethylenediamine were added in sequence, with a molar ratio of caffeic acid, ammonium persulfate, and ethylenediamine of 2:1:1, wherein the mass of ammonium persulfate was 0.633 g and the mass of ethylenediamine was 188 μL, and the mixture was stirred until uniformly mixed. HCl (7.5 mol·L -1 ) and sodium hydroxide solution (0.1 mol·L -1 ) The pH was adjusted to 6-7. After the polymerization reaction was carried out at room temperature for 2 hours, the precipitate was centrifuged, filtered and washed with deionized water, and dried at 80° C. for 12 hours. The mass of the obtained polycaffeic acid was 0.7834 g.
[0096] (2) Preparation of film casting solution: 0.1 g of polycaffeic acid was dispersed in 18.4 g of n-butanol solution, stirred at 80°C for 6 h (preferably at 800 rpm), and ultrasonicated for 2 h, then 1 g of polyether block polyamide was added to obtain a film casting solution, which was stirred at 80°C for 5 h to ensure that MAF-6 was evenly dispersed. The solution was allowed to stand at 60°C for 12 h to remove bubbles.
[0097] (3) Preparation of membrane: The PVDF base membrane was fixed on a smooth glass plate, and then the membrane-building solution prepared in (1) was slowly poured on the membrane surface and scraped (the coating thickness was set to 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80°C for 12 hours. The obtained membrane was a mixed matrix membrane doped with polycaffeic acid.
[0098] The prepared polycaffeic acid-doped pervaporation membrane (one side of the membrane coating liquid is in contact with the permeation side feed liquid) is used in the separation of volatile organic compounds as follows:
[0099] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100-150Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 1580g·m -2 ·h -1 , the separation factor is 7.7.
[0100] After adding polycaffeic acid, the hydroxyl groups in polycaffeic acid increase the affinity of the membrane surface for water molecules, slightly increasing the permeation flux, but due to the hydrophilicity of polycaffeic acid, the separation factor decreases. By adding highly hydrophobic MAF-6, the hydrophobicity of the membrane surface can be effectively improved, thereby increasing the separation factor.
[0101] Comparative Example 3:
[0102] (1) Preparation of MAF-6 nanoparticles: 1.9 g of 2-ethylimidazole was dissolved in a mixed solution of 150 ml of methanol and 10 ml of cyclohexane to obtain a 2-ethylimidazole solution. 1 g of zinc hydroxide was dissolved in 20 ml of ammonia water to obtain a zinc hydroxide solution. The zinc hydroxide solution was quickly added to the 2-ethylimidazole solution, stirred at room temperature for 2 hours, centrifuged, and the obtained white precipitate was filtered with methanol and placed in an oven at 80° C. for drying for 12 hours. 1.170 g of MAF-6 particles with a particle size of 400-500 nm were obtained.
[0103] (2) Preparation of membrane casting solution: 0.1 g MAF-6 was dispersed in 18.4 g n-butanol solution, stirred at 80° C. for 6 h (the rotation speed was preferably 800 rpm), and ultrasonicated for 2 h, and then 1 g polyether block polyamide was added to obtain a membrane casting solution, and the membrane casting solution was stirred at 80° C. for 5 h to ensure that MAF-6 was evenly dispersed. The solution was allowed to stand at 60° C. for 12 h to remove bubbles.
[0104] (3) Preparation of membrane: The PVDF base membrane was fixed on a smooth glass plate, and then the membrane-building solution prepared in (2) was slowly poured on the membrane surface and scraped (the coating thickness was set to 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80°C for 12 hours. The obtained membrane was a MAF-6-doped mixed matrix membrane.
[0105] The prepared MAF-6 doped mixed matrix membrane was applied in the separation of volatile organic compounds as follows:
[0106] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 1500g·m -2 ·h -1 , the separation factor is 12.5.
[0107] The addition of MAF-6 significantly improves the membrane separation factor, but due to the high hydrophobicity of the inner and outer pores of MAF-6, MAF-6 has a significant repulsion to water molecules, so the permeation flux is lower than that of Example 1.
[0108] Comparative Example 4:
[0109] (1) Preparation of MAF-6 nanoparticles: 1.9 g of 2-ethylimidazole was dissolved in a mixed solution of 150 ml of methanol and 10 ml of cyclohexane to obtain a 2-ethylimidazole solution. 1 g of zinc hydroxide was dissolved in 20 ml of ammonia water to obtain a zinc hydroxide solution. The zinc hydroxide solution was quickly added to the 2-ethylimidazole solution, stirred at room temperature for 2 hours, centrifuged, and the obtained white precipitate was filtered with methanol and placed in an oven at 80° C. for drying for 12 hours. 1.170 g of MAF-6 particles with a particle size of 400-500 nm were obtained.
[0110] (2) Preparation of polycaffeic acid: Preparation of polycaffeic acid: 1 g of caffeic acid was completely dissolved in deionized water at 80°C to obtain a caffeic acid solution with a solubility of 2 g / L. Then ammonium persulfate and ethylenediamine were added in sequence, with a molar ratio of caffeic acid, ammonium persulfate, and ethylenediamine of 2:1:1, wherein the mass of ammonium persulfate was 0.633 g and the mass of ethylenediamine was 188 μL, and stirred until uniformly mixed. HCl (7.5 mol·L -1 ) and sodium hydroxide solution (0.1 mol·L -1 ) The pH was adjusted to 6-7. After the polymerization reaction was carried out at room temperature for 2 hours, the precipitate was centrifuged, filtered and washed with deionized water, and dried at 80° C. for 12 hours. The mass of the obtained polycaffeic acid was 0.7834 g.
[0111] (3) Preparation of membrane casting solution: 0.1 g MAF-6 and 0.1 g polycaffeic acid were dispersed in 18.4 g n-butanol solution, stirred at 80° C. for 6 h (the rotation speed was preferably 800 rpm), and ultrasonicated for 2 h, and then 1 g polyether block polyamide was added to obtain a membrane casting solution, and the membrane casting solution was stirred at 80° C. for 5 h to ensure that MAF-6 was evenly dispersed. The solution was allowed to stand at 60° C. for 12 h to remove bubbles.
[0112] (4) Preparation of membrane: The PVDF base membrane was fixed on a smooth glass plate, and then the membrane-building solution prepared in (1) was slowly poured on the membrane surface and scraped (the coating device was set to a thickness of 60 μm). After scraping, the membrane was placed in a culture dish and placed in an oven at 80° C. for drying for 12 h. The obtained membrane was a polycaffeic acid and MAF-6 co-doped mixed matrix membrane.
[0113] The prepared polycaffeic acid and MAF-6 co-doped mixed matrix membrane is applied in the separation of volatile organic compounds as follows:
[0114] The ethanol / water solution with a concentration of 5wt% was used as the feed liquid on the permeation side. The operating conditions of the pervaporation were as follows: temperature 40°C, vacuum degree 100Pa, feed liquid volume 1L, feed rate 0.4L / min, and operation time 1h. The total permeation flux of the membrane prepared under these conditions was 1876g·m -2 ·h -1 , the separation factor is 13.
[0115] Although the separation factor of the membrane is improved by adding MAF-6 and polycaffeic acid particles, simple mechanical mixing will cause MAF-6 to agglomerate inside the membrane, which can easily cause defects on the membrane surface and affect the performance of the membrane. By pre-laying a layer of polycaffeic acid interlayer and growing MAF-6 in situ on the hydroxyl groups of polycaffeic acid, the uniform distribution of MAF-6 can be promoted to form a continuous layer, effectively improving the separation factor and permeation flux.
Claims
1. A polycaffeic acid sandwich MAF-6 based mixed matrix membrane, characterized in that: From bottom to top, it is composed of a PVDF base membrane, a polycaffeic acid interlayer with in-situ grown MAF-6, and a polymer matrix layer with dispersed MAF-6.
2. The polycaffeic acid sandwich MAF-6 based mixed matrix membrane according to claim 1, characterized in that The polymer matrix is selected from the group consisting of: polyether block polyamide, polydimethylsiloxane, and phenyltrimethoxysilane.
3. The polycaffeic acid sandwich MAF-6 based mixed matrix membrane according to claim 1, characterized in that: The polycaffeic acid is prepared by polymerization reaction of caffeic acid, ammonium persulfate and ethylenediamine, and the particle size of the polycaffeic acid is 200-1000nm.
4. The polycaffeic acid sandwich MAF-6 based mixed matrix membrane according to claim 3, characterized in that The preparation method of polycaffeic acid is as follows: The aqueous solution of caffeic acid, ammonium persulfate and ethylenediamine are mixed evenly, the pH is adjusted to 6-7, and the mixture is stirred and reacted at room temperature for 2 hours. The reaction solution is then centrifuged, and the precipitate is collected, washed and dried to obtain polycaffeic acid. The molar ratio of caffeic acid, ammonium persulfate and ethylenediamine is 2-4:1-2:1; The concentration of the aqueous solution of caffeic acid is 1 to 5 g / L.
5. The method for preparing a polycaffeic acid sandwich MAF-6 based mixed matrix membrane as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) Dispersing polycaffeic acid uniformly in deionized water, adding an ammonia solution of zinc hydroxide to adjust the pH to 6-7, and then adding an organic solution of 2-ethylimidazole to disperse uniformly to obtain a mixed system; immersing a PVDF substrate in the obtained mixed system, allowing it to stand for 1-4 hours, then taking it out and rinsing it with methanol, and drying it at room temperature to obtain a polycaffeic acid membrane of in-situ grown MAF-6; (2) dispersing MAF-6 in n-butanol, then adding the polymer matrix, stirring, and standing to obtain a membrane-building solution; (3) Fixing the polycaffeic acid film of the in-situ grown MAF-6 obtained in step (1), coating the film-building solution obtained in step (2) with a scraper, and drying to obtain the polycaffeic acid sandwich MAF-6-based mixed matrix membrane.
6. The preparation method according to claim 5, characterized in that: In step (1), the volume mass ratio of deionized water to polycaffeic acid is 16.7-33.3:1, mL / g; the mass ratio of polycaffeic acid, zinc hydroxide and 2-ethylimidazole is 1-20:10-20:
10.
7. The preparation method according to claim 5, characterized in that: In step (1), in the ammonia solution of zinc hydroxide, the concentration of zinc hydroxide is 40-80 g / L, and the concentration of the solvent ammonia is 15-28 wt %; in the organic solution of 2-ethylimidazole, the concentration of 2-ethylimidazole is 5-20 g / L, and the solvent is a mixed solvent of methanol and cyclohexane in a volume ratio of 15:
1.
8. The preparation method according to claim 5, characterized in that: In step (2), the mass ratio of MAF-6, polymer matrix and n-butanol is 0.01-0.2:1:15-20.
9. The polycaffeic acid sandwich MAF-6-based mixed matrix membrane as claimed in claim 1 is used for pervaporation recovery of alcohol from alcohol aqueous solution.
10. The use according to claim 9, characterized in that The alcohol is ethanol.
Citation Information
Patent Citations
Preparation method of pervaporation layer-by-layer assembled membrane for gasoline desulfurization
CN110327782A
Preparation method of PDMS-based pervaporation membrane with continuous intermediate layer
CN116726719A
Carbonized ZIF-8 doped Pebax derived carbon film as well as preparation method and application thereof
CN118304770A
Cation exchange membrane comprising copolymer containing cation exchange group
KR1020120035565A
Sustained-release antibacterial film and preparation method thereof
US20240199826A1